Menuju Desa Konservasi Aggrek di Desa Ngresep Balong, Limbangan Kendal - Endah Rita Sulistya Dewi; Ary Susatyo Nugroho; Maria Ulfa (Journal of Dedicators Community, 2018)
Forest Ungaran Mountain has a variety of plant diversity, one of which is a kind of forest orchids. Along with the wild hunting of Ungaran Mountain orchard and the change of function and clearing of forest land, then the popuasi and natural habitat for Ungaran Mountain Orchid species increasingly reduced. This makes the villagers of Ngesrep Balong feel worried about the species will disappear or extinct. To anticipate this, the villagers realized that the effort to conserve orchid of Ungaran Mountain needs to be done. The main problem is that villagers do not have enough skills to do conservation effort independently. Therefore it is very necessary to do counseling and training through this PPDM activity so that villagers gain knowledge and skills in conducting activities of conservation, cultivation until production of Ungaran Mountain Orchid independently. At Mount Ungaran Resort Limbangan Kendal District, found 12 species of orchids derived from 8 genera. Of the 12 species are 10 species of which are orchids epiphytes and two other types of terrestrial orchids. Looking at the potential, it can be concluded that Ngesrep Balong Village has potential to be used as Conservation Village of Orchid